DEMAND RESPONSE MANAGEMENT FOR SMART GRID USING HYBRID TRUST MODEL BASED ON BLOCKCHAIN - Isah, Muhammad Jibrin; Yahaya, Adamu Sani; Garba, Ahmad Tijjani; Ahmad, Hafsa Kabir (FUDMA Journal of Sciences, 2025)
Blockchain technology improves smart grid demand response by enhancing the security and efficiency of energy trading, especially for distributed resources such as electric vehicles, thereby enabling more reliable and effective management of energy transactions across different and decentralized networks. Existing models face challenges such as high computational overhead, inconsistent block creation times, and vulnerabilities to malicious entities, which hinder practical implementation. This study develops a hybrid trust model integrating attribute-based authentication and reputation-based trust within a blockchain framework to optimize performance and security for real-time smart grid operations. A simulation involving 190 entities (10 industries, 50 residences, 30 buildings, and 100 electric vehicles) with over 1000 transactions was conducted using a Python script. The model employed parallel Proof of Work with a difficulty of 2, 10 miner nodes, and a thread pool for distributed computation. The simulation achieved a 91.80% authentication success rate, an average computational time of 3.60 milliseconds, a block creation time of 42.10 milliseconds, and a throughput of 12.39 blocks per second, outperforming the baseline’s 63.8 milliseconds block time and 15.6 transactions per second. Inconsistent node performance and a basic trading model without distance-based loss calculations reduce the model’s security and economic precision. This research contributes to the development of blockchain-based demand response systems by providing a scalable foundation for secure and efficient energy trading in smart grids, enabling broader application and improved system reliability.
Keywords: Blockchain; Demand Response; Smart Grid; Hybrid Trust Model; Smart Contracts